2022
DOI: 10.1021/acsomega.1c07267
|View full text |Cite
|
Sign up to set email alerts
|

Loading of Coal Tar in Polymeric Nanoparticles as a Potential Therapeutic Modality for Psoriasis

Abstract: Coal tar (CT) is a commonly used therapeutic agent in psoriasis treatment. CT formulations currently in clinical use have limitations such as toxicity and skin staining properties, leading to patient nonadherence. The purpose of this study was to develop a nanoparticle (NP) formulation for CT based on biocompatible poly(lactide- co -glycolide) (PLGA). CT was entrapped in PLGA NPs by nanoprecipitation, and the resulting NPs were characterized using dynamic light scattering and high-perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…PLGA, due to its low toxicity and degradability, is used in cosmetics for gentle, gradual delivery of unstable substances such as vitamin C, urea, etc. on the human skin. Besides, it has been demonstrated that PLGA-based nanomedicine shows promising results in treating many skin diseases, including psoriasis and melanoma. , The working mechanism behind the drug design is that lipophilic nanoparticles like PLGA will have a much higher affinity to the skin and therefore enhance the delivery efficiency of many hydrophilic drugs. There has been a debate in the community over whether 100 nm nanoparticles are able to enter the skin and if they do, whether they could maintain their colloidal stability …”
Section: Topical Delivery: Skinmentioning
confidence: 99%
“…PLGA, due to its low toxicity and degradability, is used in cosmetics for gentle, gradual delivery of unstable substances such as vitamin C, urea, etc. on the human skin. Besides, it has been demonstrated that PLGA-based nanomedicine shows promising results in treating many skin diseases, including psoriasis and melanoma. , The working mechanism behind the drug design is that lipophilic nanoparticles like PLGA will have a much higher affinity to the skin and therefore enhance the delivery efficiency of many hydrophilic drugs. There has been a debate in the community over whether 100 nm nanoparticles are able to enter the skin and if they do, whether they could maintain their colloidal stability …”
Section: Topical Delivery: Skinmentioning
confidence: 99%
“…The amphiphilicity of this copolymer leads to the formation of micelles in aqueous solutions, where the hydrophobic core contains PPO blocks and the hydrophilic surface layer is comprised of PEO blocks. [ 6 7 8 9 10 11 12 13 14 15 ]…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…The matrix based nanospheres, shell based nano capsules highly branched dendrimers, and the gel emulsifiers are different form PNPs. Enhanced circulation in the body, longer adherence, reduced side effects, non-allergic formulations, biocompatibility, bioavailabilty and biodegradability properties makes them suitable for topical application [53][54][55] .…”
Section: Polymeric Nanoparticles (Pnps)mentioning
confidence: 99%